(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper we introduce a novel application of cordial labeling using the fifth power of graphs, demonstrating its potential for understanding and studying specific graph structures. The resulting cordial labeling scheme for the fifth power of paths, cycles, fans, wheels, lemniscate and the union of fifth power of paths and cycles graphs can provide insights into the properties and structures of these graphs. It can be used to analyze its connectivity, symmetry, and other graph-theoretical characteristics.